The Factors of Strategic Leadership on Commitment: An Empirical Banking in Indonesia - Noor, Juliansyah (Universitas Prasetiya Mulya, 2013)
This research is aimed at obtaining information related to possibility whether organizational commitment is affected by training, organization culture, and ethical practice. The data which had been analyzed by multi regression analysis after all variables had been put into principal factor analysis. In this research employees were chosen as a unit analysis and 120 samples selected randomly. The result of this study shows that organization commitment is positively affected by training, organization culture and ethical practice. Implications of organization commitment might have been effected by training, organization culture and ethical practice as a strategic leadership.